Performance Study of mmWave Beamspace MU-MIMO-NOMA Communication System - Pal R.; Sarawadekar K.P. (My University, 2025)
We are considering a millimeter wave (mmWave) beamspace multi-user MIMO (MU-MIMO) small-cell communication system which suffers from high radio frequency (RF) complexity. To reduce RF complexity, a beam selection technique is deployed at the access point. However, each beam requires a single dedicated RF chain correspond to each user. Thus, the beam selection technique selects distinct beams to each user without significant loss. To reduce the RF complexity further, 'a beam selection algorithm accompanied by nonorthogonal multiple access (NOMA) principle followed with a power allocation scheme' is proposed. As a result, it can serve multiple users through a single beam. Hence, it reduces required number of RF chains. In addition, selecting the same beam for conflict users will also reduce interference to each other, and will improve the system performance. Finally, we are investigating the system which demonstrates an excellent performance with the less number of RF chains than the existing systems. © 2019 IEEE.